Analysis of the Causes of Burnout in Nurses and Its Implications on Productivity - Novianti, Tria Nisa; Budiyanto, Tri (Universitas Ibn Khaldun Bogor, 2025)
Burnout is a condition often experienced by nurses due to chronic workplace stress. This condition is characterized by symptoms of emotional exhaustion, depersonalization, and low personal accomplishment, which impact work productivity and the quality of healthcare services. This study aims to identify the risk factors for burnout among nurses through a systematic literature review. The research method follows the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), with article searches on Google Scholar, PubMed, and Semantic Scholar, and using specific inclusion criteria. A total of 9 articles were analyzed to gather information on burnout risk factors. The research findings show that the main risk factors for burnout include high workload, long working hours, lack of social support, and education level. Demographic factors such as age and work experience also influence burnout risk. Additionally, working in intensive care units, marital status, and having a diploma education increase susceptibility to burnout. Burnout affects the intention to quit work, reduces productivity, and impacts the quality of healthcare services. Management strategies such as workload management, social support, and mental health training and stress management programs are needed to address burnout. These steps are crucial for improving nurse well-being, maintaining the quality of healthcare services, and reducing workforce turnover.